Financial incentives for whistleblowers: A short survey - Giancarlo Spagnolo; Theo Nyreröd (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2019)
Whistleblower reward programs, or "bounty regimes", are increasingly used in the United States. The effectiveness of these programs have been questioned, and empirical evidence on their effectiveness have been scarce likely due to their relatively recent introduction. In recent years, however, empirical and experimental evidence on their effectiveness have become more available and robust. We review the (rather encouraging) evidence on whistleblower reward programs, in terms of amount of additional information generated, deterrence effects, and administration costs, and consider the possibility of extending them to accomplice-witnesses in antitrust.
Keywords: B26; 330; whistleblowers; economy